Use of a Fungicide to Reduce Stomatal Conductance in Sweet Corn Planted at Different Populations with Limited Irrigation - D. W. Sweeney; M. B. Kirkham (Kansas Agricultural Experiment Station Research Reports, 2016)
In 2015, increasing seeding rates increased the number of harvested sweet corn ears; however, total fresh weight did not increase above 22,500 seeds/acre. Sweet corn was little affected by limited irrigation or a fungicide applied for stomatal control.
Keywords: sweet corn